Opto-biomechanical simulation of keratoconus development in emmetropic eyes - Ghaderi, Hosna; García, Marta Jiménez; Koppen, Carina; Rozema, Jos (Journal of optometry, 2025)
To assess how different corneas respond to a standardized structural weak spot in different sizes and locations using the finite element method depending on their initial geometry. The corneal meshes of 5 randomly selected emmetropic SyntEyes with different biometry and optical properties were generated using MATLAB and ANSYS. To simulate keratoconus development, a local stiffness reduction of up to 60 % of the original value was implemented in three locations (central, 1mm, and 2mm inferior) with a diameter of 2mm for each cornea. From this, tangential corneal power maps were calculated. Local weakening causes the formation of a conical deformation at the site of the weak spot and, for an inferior weak spot, a superior flattening. At the center of the weak spot, the cornea becomes thinner by 50μm, while the maximum anterior curvature increased by an average of 51.76±1.38D and the posterior curvature by an average of -7.45±0.15D for the central keratoconus. The anterior surface area increases by 0.88±0.29 mm² and 0.85±0.03 mm² for a central and inferior keratoconus, respectively. The corresponding values for the posterior surface were 1.10±0.03 mm² and 1.06±0.03 mm². The shape of a keratoconic cornea is not only determined by the response to a local structural weakening, but also by its original corneal shape. This understanding may help enhance early detection and monitoring techniques for keratoconus progression.